Import substitution of combination wire rope. Part 3: Comparison of standard Cift-CWR and imported combination wire rope - Panicker, P.A., Meenakumari, B. and (Fishery Technology, 2021)
Tensile and extension properties of standard Cift-CWR and imported combination wire ropes from Japan, Norway and Denmark are studied and the analysis is presented in the paper. Tensile and chemical properties of steel wire, tensile and abrasive properties of PP covering, effect of twist on material at different stages are worked out and reported.